Ultrasound Assisted Solvent Free Intercalation of Montmorillonite with PEG1000: A New Type of Organoclay with Improved Thermal Properties - Önder, Emel; Ukuşer, Gökçen; Öztürk, Mehmet; SARIER, NİHAL; ARAT, REFİK (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2013)
This study investigates the intercalation of low molecular weight poly(ethylene glycol), PEG1000, into a montmorillonite-type Anatolian clay mineral (MMTA) using ultrasound sonication in a solvent free medium to produce a new type of organoclay with improved thermal properties. The results from the particle size distribution and X-ray diffraction (XRD) analyses of the PEG-MMT composites revealed that the ultrasonication process caused a significant reduction in the size of MMTA without destroying its crystalline structure. The XRD results also revealed that PEG1000 was successfully intercalated into the galleries of MMTA. The best PEG-MMT composites have a particle size distribution that ranges between 396 and 1280 nm, and they provide a heat storage capacity of 104.8 Jg(-1) at -32.9 to 43.0 degrees C and heat release capacity of 107.0 Jg(-1) at 27-17.2 degrees C. The thermal cyclic analyses indicated that no degradation or segregation of PEG1000 occurred within the composites. The ultrasound sonication in a solvent free medium can be suggested to be an effective modification route for the intercalation of MMT using nontoxic and biocompatible PEGs during the production of organoclays. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: PEG; montmorillonite; organoclay; thermal; ultrasound; layered silicate nanocomposites; phase-change materials; poly(ethylene oxide); polyethylene-glycols; nonionic surfactants; melt intercalation; molecular-weight; clay; chemistry; organokil; termal; ultrason; katmanlı silikat nanokompozitleri; faz değiştirme malzemeleri; poli (etilen oksit); polietilen-glikoller; noniyonik sürfaktanlar; erime interkalasyonu; moleküler ağırlık; kil; kimya